2011
DOI: 10.1007/s10571-011-9733-y
|View full text |Cite
|
Sign up to set email alerts
|

Orexin A in Cortical Cultures: Expression and Effect on Synaptogenesis During Development

Abstract: Orexin A (OXA) is an excitatory hypothalamic neurotransmitter and ligand for Orexin Receptor-1 (OR1), isolated from a small group of hypothalamic neurons. OXA orchestrates different brain functions, and at the cognitive level some of the effects of insufficiency of OXA are well-known, for example in Parkinson’s disease. It is widely assumed that deteriorated cognitive processes are related to impaired network connectivity. However, little is known about the effects of OXA in network connectivity and synaptogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Consistent with this finding our results and published experimental studies [34, 53] show that ischemic stroke induces increased expression of Ox1R in the brain, which correlates with decreases of OXA in cerebrospinal fluid as an adaptive response to maintain OXA supply to the brain. Finally, a recent study showed that in some conditions such ischemic stroke, cortical neurons may homeostatically switch to the production of OXA as an adaptation mechanism [54]. This observation is consistent with the notion that re-mapping processes that spontaneously occur after stroke [55, 56] may induce an early change of genes expression, and OX and MCH systems may be involved in this process.…”
Section: Discussionsupporting
confidence: 80%
“…Consistent with this finding our results and published experimental studies [34, 53] show that ischemic stroke induces increased expression of Ox1R in the brain, which correlates with decreases of OXA in cerebrospinal fluid as an adaptive response to maintain OXA supply to the brain. Finally, a recent study showed that in some conditions such ischemic stroke, cortical neurons may homeostatically switch to the production of OXA as an adaptation mechanism [54]. This observation is consistent with the notion that re-mapping processes that spontaneously occur after stroke [55, 56] may induce an early change of genes expression, and OX and MCH systems may be involved in this process.…”
Section: Discussionsupporting
confidence: 80%
“…Importantly, intravenous or intranasal administration of orexin-A to non-human primates rescues cognitive impairments due to sleep-deprivation ( Deadwyler et al, 2007 ). The protection of orexin-A on cognition is considered to be relevant with enhancing long-term potentiation ( Wayner et al, 2004 ; Akbari et al, 2008 , 2011 ), and positively related to the neurogenesis and synaptic plasticity in hippocampus ( Stoyanova et al, 2010 , 2012 ; Yang et al, 2013 ; Zhao et al, 2014 ). In present study, we demonstrated that chronic i.c.v.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, orexins promote synaptogenesis, network development, and maturation. In cultures of cortical neurons, orexin A acts as synaptogenic factor promoting neural interactions [Stoyanova et al, 2012]. Although the detailed molecular mechanism remains to be elucidated, the indirect upregulation of neurotrophic factors like neurotrophin-3 could explain this action [Yamada et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these 'classical' functions, orexins have been proposed as important signaling molecules during brain development and maturation, being related to synaptogenesis and neuroprotection Stoyanova et al, 2010Stoyanova et al, , 2012. In contrast with the relatively abundant literature on orexins in the adult brain, there are few studies about the role of these neuropeptides in the developing brain of vertebrates.…”
mentioning
confidence: 99%